Asuhan Keperawatan Pada Ny.S Dengan Diabetes Melitus Tipe 2 Melalui Penerapan Teknik Relaksasi Benson - Irvando Islami; Nila Kusumawati; Riani Riani (Excellent Health Journal, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder that occurs because the body does not have enough insulin hormone due to disorders in insulin secretion or insulin hormone that does not work properly or both. DM can cause various impacts, ranging from mild problems to serious life-threatening complications. Some of the main impacts of DM include damage to blood vessels, nerves, eyes, kidneys, and cardiovascular problems such as heart disease, stroke, and peripheral vascular disease. One of the non-pharmacological therapies to overcome DM is Benson relaxation therapy. The purpose of the study was to provide nursing care through the provision of Benson relaxation therapy to reduce blood glucose levels in DM patients. The sampling technique was purposive sampling. The sample in this study was Mrs. S. The study was conducted on May 27-31, 2024. Therapy was carried out for 3 consecutive days. Blood sugar measurements on the first day were 290 mg/dL, blood sugar measurements on the third day after being given the Benson relaxation technique were 212 mg/dL. The results of the study showed a decrease in blood glucose levels of 18 mg/dL. It is hoped that nurses can carry out Benson relaxation therapy to reduce blood glucose levels in patients with DM.